Hyperlink desirability in adolescent fiction: location and absorption. Issue 3 (4th March 2023) - Vanhees, Claudio; Simons, Mathea; Joosen, Vanessa
Abstract: In the digital age, children's and adolescents' willingness to engage in absorbed reading for pleasure is on the decline. Digital narratives with a linear storyline enriched with hyperlinks to supporting media materials, could potentially facilitate narrative absorption even better than print, thus stimulating fictional reading among adolescents. This paper examines hyperlink placement desirability in five full-length novels, and investigates the link with narrative absorption. It was found that, independently of genre, the desired hyperlinks were most concentrated in the first quartile of the story, and gradually diminished towards quartile four. Furthermore, closer scrutiny of one case study showed that as reported narrative absorption levels increased, hyperlink desirability decreased. The results suggest that hyperlinks to different types of supporting media materials could be particularly useful to assist reading if situated in the first quartile of digital narrative. As the story plot reaches its climax, hyperlinks may become less required for experienced readers, whereas lower ability readers might still benefit from their support to sustain the reading experience.